Preparation method of aluminum alloy matte sand surface oxidation film layer

Through the process flow of sandblasting pretreatment, alkaline polishing, anodizing and post-treatment, the wear resistance, insufficient corrosion resistance and large color difference of the oxide film layer of aluminum alloy components is solved, and the surface treatment of aluminum alloy components is achieved is achieved, which is suitable for special optoelectronic equipment and other scenarios.

CN119640367APending Publication Date: 2025-03-18HENAN PINGYUAN OPTO ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411663401.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the oxide film layer of aluminum alloy components has insufficient wear resistance and corrosion resistance, large color difference, strong reflection and easy light pollution, and the acid polishing process is high and easy to cause environmental pollution.

Method used

Using sandblasting pretreatment process, alkaline chemical polishing, anodizing and post-treatment process, an aluminum alloy matte sand-surface oxide film layer with good corrosion resistance, wear resistance and uniform coloring is prepared by selecting sand materials, dyes and process parameters.

Benefits of technology

The corrosion resistance and wear resistance of the oxide film layer of aluminum alloy components are improved, and the color difference is uniform, light pollution is avoided, and the process cost is low and environmentally friendly, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640367A_ABST
    Figure CN119640367A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an aluminum alloy matte sand surface oxidation film layer, belongs to the technical field of metal surface treatment, and solves the problems that in the prior art, an oxidation film layer is insufficient in wear resistance and corrosion resistance, large in color difference and high in reflection, light pollution is easily caused, and an adopted acid polishing process is high in cost and easily causes environmental pollution. The invention provides a preparation method of an aluminum alloy matte sand surface oxidation film layer. A part with the aluminum alloy matte sand surface oxidation film layer is obtained after sand blasting pretreatment, alkaline chemical polishing, anodic oxidation, dyeing and sealing treatment. A polishing solution adopted in alkaline chemical polishing contains sodium hydroxide, sodium nitrate, copper sulfate pentahydrate and triethanolamine. The preparation method is simple in process, green, environment-friendly and low in cost; and the prepared oxidation film layer has good alcohol resistance and corrosion resistance. The color is high in quality and uniform, the frosted texture is good, light pollution is not generated, and the method can be widely applied to optical systems and instruments in aerospace, field scientific investigation and other scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface treatment, and in particular to a method for preparing an oxide film layer on a matte sand surface of an aluminum alloy. Background Art

[0002] In recent years, with the continuous development of various optoelectronic equipment, special optoelectronic equipment such as bionic cameras, monitoring equipment, infrared rangefinders, infrared night vision devices, etc., in addition to the requirements of performance indicators, also have strict requirements on appearance quality, that is, they need higher corrosion resistance and wear resistance, and have beautiful texture effects. They must be able to integrate well into the surrounding environment to avoid secondary pollution such as light pollution or disturbing wild animals during scientific expeditions.

[0003] Based on both economic and performance considerations, the above-mentioned equipment mostly uses aluminum alloy to prepare exposed parts or shells, and generally adopts a matte sand surface black effect, thereby achieving a good effect of avoiding reflection and integrating into the environment. At present, the conventional surface treatment method for aluminum alloy parts is anodizing followed by spraying or painting.

[0004] As a conventional surface treatment protection method, anodizing can meet conventional anti-corrosion requirements, but the matte sand surface effect requires specific pre-treatment methods for anodized parts. The current conventional pre-treatment method is acid polishing, which is difficult to operate and has high solution preparation costs. In addition, the process will produce irritating nitrogen oxides that pollute the environment. In addition, the oxide film produced by conventional technology cannot meet the corrosion resistance requirements in special scenarios such as field scientific research and aerospace, and has appearance defects such as uneven coloring and easy fading. Summary of the invention

[0005] In view of the above analysis, an embodiment of the present invention aims to provide a method for preparing an oxide film layer on a matte sand surface of an aluminum alloy, so as to solve at least one of the problems of the oxide film layer prepared by the conventional method in the prior art, such as insufficient wear resistance and corrosion resistance, large color difference, strong reflection, which is easy to cause light pollution, and the acid polishing process used is high in cost and easy to cause environmental pollution.

[0006] The present invention provides a method for preparing an aluminum alloy matte sand surface oxide film layer, which comprises the following steps: firstly, the aluminum alloy to-be-processed part is subjected to sandblasting pretreatment and alkaline chemical polishing; then, an anodic oxidation process is adopted to prepare a matte sand surface oxide film layer substrate; finally, the substrate is subjected to dyeing and sealing treatment to obtain a part having an aluminum alloy matte sand surface oxide film layer;

[0007] The polishing liquid used in the alkaline chemical polishing contains sodium hydroxide, sodium nitrate, copper sulfate pentahydrate and triethanolamine.

[0008] Specifically, the contents of the components of the polishing liquid are: 240-260 g / L of sodium hydroxide, 265-285 g / L of sodium nitrate, 2-3 g / L of copper sulfate pentahydrate, 10-20 ml / L of triethanolamine, and the solvent is water.

[0009] Specifically, the specific process parameters of the alkaline chemical polishing are a polishing temperature of 62° C. to 68° C. and a polishing time of 16 to 20 seconds.

[0010] Specifically, the sandblasting pretreatment process uses 80-100 mesh white corundum, and the sandblasting pressure is 0.5 MPa-0.6 MPa.

[0011] Specifically, the anodic oxidation process uses an oxidation solution of 200-220 g / L sulfuric acid, an oxidation temperature of 15° C.-20° C., an oxidation voltage of 12 V, and an oxidation time of 60 min.

[0012] Specifically, the dyeing process parameters are: dyeing temperature 10°C to 40°C, and dyeing time 10min to 30min.

[0013] Specifically, the sealing solution used in the sealing process is 5-10 g / l ODM SEAL EX sealing powder, the sealing temperature is 70° C.-90° C., and the time is 10 min-15 min.

[0014] Specifically, the aluminum alloy model is one of 6061, 6063, 7A04 and 7075.

[0015] Specifically, the dye used in the dyeing process is YM-690, and the color is black.

[0016] The present invention also discloses an aluminum alloy component with a matte sand surface oxide film, wherein the oxide film of the aluminum alloy component is prepared by the above-mentioned preparation method; the component is immersed in 95% ethanol, and the color of the oxide film does not change after 2 hours; no corrosion occurs in a salt spray test for 96 hours; and no corrosion occurs in a wet heat test for 240 hours.

[0017] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0018] 1. The present invention adopts an alkaline polishing process to replace an acid polishing process to polish the sand surface (formed by a sandblasting process), which has good polishing effect, low cost, and is green and environmentally friendly.

[0019] Traditional chemical polishing achieves the purpose of polishing by using the polishing solution to form and dissolve the film layer on the microscopic concave and convex surface of the workpiece at different rates. In the alkaline polishing solution, the main function of sodium hydroxide is to corrode and dissolve the film layer on the surface of the aluminum alloy workpiece. Sodium nitrate plays a role in slowing down the corrosion rate and improving the flatness during the polishing process. Copper sulfate pentahydrate increases the brightness of the polished surface and enhances the polishing effect. Triethanolamine is used to improve the polishing environment and inhibit the overflow of nitrogen oxides.

[0020] The experiment proves that the polishing uniformity is good, no structural defects are generated, the surface finish is good, no toxic and irritating gas is generated during the whole polishing process, the cost is controllable, and it is safe and environmentally friendly. Particularly preferably, when the recommended parameters are adopted for implementation, better results can be obtained.

[0021] 2. The present invention adopts the oxide film preparation process of "sandblasting pretreatment process - alkaline polishing - anodizing - post-treatment", selects suitable sand materials, dyes and other raw materials, and optimizes the process parameters. The oxide film finally obtained has good corrosion resistance, alcohol resistance and uniform and firm coloring.

[0022] The sandblasting pretreatment plus alkaline polishing process can not only achieve the matte effect required by the optical system, but also make the substrate surface more delicate, uniform and smooth. Combined with the preferred anodizing process, the pore size and thickness of the anodized film layer can be made more uniform, so that the final dyeing and sealing can obtain a film layer with a delicate, soft and uniform color and good corrosion resistance and alcohol resistance.

[0023] The treated parts were immersed in 95% ethanol for 2 hours, and the color of the oxide film did not change. The salt spray test lasted for 96 hours, and no corrosion occurred. The wet heat test lasted for 240 hours, and no corrosion occurred (such as Figure 5 shown).

[0024] 3. The oxide film preparation process provided by the present invention is simple, has low operating difficulty, good product stability, and is suitable for large-scale production and wide promotion.

[0025] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0027] Figure 1Actual photos of colored aluminum alloy parts;

[0028] Figure 2 The actual photos of the polished samples in the polishing formula and polishing process parameter experimental group (experimental group 2);

[0029] Figure 3 This is a photo of the sample (dyed) in the anodizing formula and oxidation parameter experimental group (experimental group 3);

[0030] Figure 4 This is a photo of the sample after sandblasting pretreatment in the sandblasting process parameter experimental group (experimental group 1). Figure 4 a is 1-1-2, Figure 4 b is 1-1-5, Figure 4 c is 1-3-5;

[0031] Figure 5 Actual photos of the oxide film performance test of colored aluminum alloy parts. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0033] The present invention provides a method for preparing an oxide film layer on a matte sand surface of an aluminum alloy. Firstly, the aluminum alloy workpiece to be processed is subjected to sandblasting pretreatment and alkaline chemical polishing.

[0034] Then, an anodic oxidation process is used to prepare a matte sand surface oxide film substrate;

[0035] Finally, the substrate is dyed and sealed to obtain a component with an aluminum alloy matte sand surface oxide film layer;

[0036] The present invention adopts the oxide film preparation process of "sandblasting pretreatment process - alkaline polishing - anodizing - post-treatment", selects suitable sand materials, dyes and other raw materials, and optimizes the process parameters. The oxide film finally obtained has good corrosion resistance and alcohol resistance, and the coloring is uniform and firm.

[0037] The sandblasting pretreatment plus alkaline polishing process can not only achieve the matte effect required by the optical system, but also make the substrate surface more delicate, uniform and smooth. Combined with the preferred anodizing process, the pore size and thickness of the anodized film layer can be made more uniform, so that the final dyeing and sealing can obtain a film layer with a delicate, soft and uniform color and good corrosion resistance and alcohol resistance.

[0038] The invention adopts an alkaline polishing process to replace an acid polishing process to polish a sand surface (formed by a sandblasting process), has good polishing effect, low cost and is green and environmentally friendly.

[0039] Specifically, the polishing liquid used in the alkaline chemical polishing contains sodium hydroxide, sodium nitrate, copper sulfate pentahydrate, and triethanolamine.

[0040] Specifically, the contents of the components of the polishing liquid are: 240-260 g / L of sodium hydroxide, 265-285 g / L of sodium nitrate, 2-3 g / L of copper sulfate pentahydrate, 10-20 ml / L of triethanolamine, and the solvent is water.

[0041] The role and content of each component in the polishing liquid are determined as follows:

[0042] Sodium hydroxide: corrodes and dissolves the surface of the substrate. Too little will affect the polishing efficiency and polishing brightness, while too much will easily cause over-corrosion and affect the size of parts. Experimental verification shows that 240-260g / L of sodium hydroxide is appropriate.

[0043] Sodium nitrate: relieves substrate corrosion and improves surface smoothness. Too much polishing reduces brightness, while too little polishing makes the surface uneven and prone to marks. Experimental verification shows that 265-285g / L of sodium nitrate is appropriate.

[0044] Copper sulfate pentahydrate: increases the brightness of the substrate surface. Too much or too little polishing will reduce the brightness and the surface is prone to marks. Experimental verification shows that 2 to 3 g / L of copper sulfate pentahydrate is appropriate.

[0045] Triethanolamine: Improves the polishing environment and inhibits the overflow of nitrogen oxides. Too much will inhibit the reaction and reduce the polishing brightness, while too little will cause nitrogen oxides to volatilize. Experimental verification shows that 10-20 ml / L of triethanolamine is appropriate.

[0046] The above components work together in the polishing process, and combined with specific processes and supporting parameters, the reaction rate and intensity are controlled within a reasonable range to achieve green, environmentally friendly, and high-quality surface polishing.

[0047] Specifically, the specific process parameters of the alkaline chemical polishing are a polishing temperature of 62°C to 68°C, such as 62, 63, 64, 65, 66, 67, 68°C, and a polishing time of 16 to 20s, such as 16, 17, 18, 19, 20s. If the polishing temperature is too high, the parts will be over-corroded, resulting in corrosion spots or pits on the surface of the parts. If the temperature is too low, it will affect the surface polishing effect. The setting of the polishing time takes into account the polishing effect and the impact on dimensional accuracy. If the time is too long, the part size will be affected by excessive corrosion, and if the time is too short, the polishing effect cannot be achieved. The sandblasted layer after polishing has a good surface finish, no structural defects, uniform and beautiful appearance, and excellent matting performance.

[0048] Specifically, the sandblasting pretreatment process uses 80-100 mesh white corundum, and the sandblasting pressure is 0.5MPa-0.6MPa. If the sand material mesh is too large, the surface sand grain size will be large, which will easily cause a violent subsequent polishing reaction and destroy the appearance consistency. If the sand material mesh is too small, the sand surface effect will not be achieved, resulting in an uneven sand surface effect.

[0049] Specifically, the anodic oxidation process uses an oxidation solution of 200-220 g / L sulfuric acid, an oxidation voltage of 12 V, an oxidation temperature of 15° C.-20° C., and an oxidation time of 60 min.

[0050] It is worth noting that the film layer prepared by the above process has uniform thickness and good bonding strength between the film layer and the substrate. The thickness of the film layer of the anodized specimen was measured and counted by an eddy current thickness gauge. The three-point method was used to measure three sets of data on each specimen surface and take the average value. The average thickness was 10-15μm. The grid method was used to determine the bonding strength. On the anodized film, 20 small squares of uniform size were scratched with a sharp blade at a spacing of 1mm (to ensure that the scratch depth exceeds the thickness of the film layer), and the number of squares that fell off was counted N1. A transparent tape was pasted on the grid area on the film and pushed with a heavy object 5 times to ensure that the tape and the film were tightly bonded, and then it was lifted up and the number of small squares that fell off was observed and counted N2. The evaluation method is as follows: Using the percentage system, the bonding strength score between the film layer and the substrate is G=100-(N1+N2). The film bonding strength score is G=100.

[0051] Specifically, the dyeing process parameters are: dyeing temperature 10°C to 40°C, and dyeing time 10min to 30min.

[0052] Specifically, the sealing solution used in the sealing process is an aqueous solution of 5-10 g / l ODM SEAL EX sealing powder, the sealing temperature is 70° C. to 90° C., and the time is 10 min to 15 min.

[0053] Specifically, the aluminum alloy model is one of 6061, 6063, 7A04 and 7075.

[0054] Specifically, the dye used in the dyeing process is YM-690, and the color is black.

[0055] Specifically, the dyeing process has high coloring quality. The experiment was carried out using the dye absorption method, and 1% alizarin red aqueous solution was dripped onto the surface of the test piece. After 5 minutes, it was washed, dried and observed, and the surface color of the colored oxide film did not change significantly; the sand surface state after coloring was basically consistent and the blackness was close.

[0056] The invention also discloses an aluminum alloy component with a matte sand surface oxide film, and the oxide film of the aluminum alloy component is prepared by the above preparation method.

[0057] Specifically, the matte sand surface oxide film has good alcohol resistance. The colored test piece was immersed in 95% ethanol and taken out after 2 hours. The color of the oxide film did not change. The dye absorption method was used to conduct an experiment. A 1% alizarin red aqueous solution was dripped onto the surface of the test piece. After 5 minutes, it was washed, dried and observed. There was no obvious change in the surface color of the colored oxide film. The corrosion resistance was good. No corrosion occurred in the salt spray test for 96 hours. No corrosion occurred in the wet heat test for 240 hours.

[0058] Specifically, the salt spray test conditions are as follows: test solution: sodium chloride solution (50±5) g / L; test temperature: (36±2)℃; pH value of salt solution: 6.5~7.2; fog drop: 1-2m1 / h / 80cm; spray time: continuous spray test duration: 240h. Test results: no color change, no corrosion spots or peeling.

[0059] Specifically, the conditions of the wet heat test and salt spray test are as follows: the temperature is raised from 30℃ to 60℃ in 2h, and the relative humidity is 95%; the temperature is kept at 60℃ and the relative humidity is 95% for 6h; the temperature is lowered from 60℃ to 30℃ in 8h, and the relative humidity is 85% to 95%, and then kept at 30℃ and the relative humidity is 95% for 8h. The above process is a cycle, and the observation is made every 24h. The experimental duration is 240h. Experimental results: no color change, no corrosion spots or peeling.

[0060] Sandblasting process parameters experimental group-experimental group 1

[0061] White corundum abrasives with different mesh sizes were used to perform sandblasting experiments at different pressures, and the visual effects of the sand grains were compared. The experimental methods are shown in the table below, and the effects of some sandblasting are compared in the table below. Figure 4 .

[0062] Table 1 Sandblasting experiment process parameters

[0063]

[0064] Different abrasive meshes correspond to different X numbers. For example, when the sandblasting pressure is 0.3-0.4MPa and the abrasive mesh is 100-120, the corresponding numbers are 1 (sandblasting process parameter experimental group)-2 (sandblasting mesh group 2)-3 (sandblasting pressure group 3). After many comparisons, it was determined that the white corundum abrasive used for sandblasting is 80-100 mesh and the sandblasting pressure is 0.5MPa-0.6MPa. The surface gloss and sand grain of the parts are moderate, and the appearance is ideal.

[0065] Polishing formula and polishing parameters experimental group - experimental group 2

[0066] Through experimental comparative analysis, the optimal polishing method and process parameters were determined, and the polishing process formula is shown in Table 2.

[0067] Table 2 Polishing process formula range

[0068]

[0069] Use the orthogonal experimental method to determine the temperature and time of chemical polishing. Select four levels of temperature A: A1 = 55℃ ~ 61℃; A2 = 62℃ ~ 68℃; A3 = 69℃ ~ 75℃; A4 = 76℃ ~ 82℃; four levels of time B: B1 = 10S ~ 15S; B2 = 16S ~ 20S; B3 = 21S ~ 25S, B4 = 26S ~ 30S; formulate the factor level table as shown in Table 3; use L 16 (4 2 ) The orthogonal table for the experiment is shown in Table 4.

[0070] Table 3 Factor level table

[0071]

[0072] Table 4L16(42) orthogonal table

[0073]

[0074] According to the appearance of polished and oxidized parts (scoring criteria: whether the gloss is uniform (40 points), whether there are marks (spots and stripes) (30 points), and whether there are corrosion pits (30 points), a process parameter experimental result analysis table is formulated, with a full score of 100 points, see Table 5.

[0075] Table 5 Process parameter experimental results analysis table

[0076]

[0077]

[0078] Results Analysis

[0079] All experimental group numbers are prefixed with 2-XXX, where 2 represents experimental group number 2.

[0080] ②Intuitive analysis: From the experimental results, the experimental result No. 5 is the best solution: 2-A2B2

[0081] (It can also be numbered 2-6. To facilitate orthogonal comparison, it is more convenient to number with letters).

[0082] ②Calculation and analysis: From the perspective of contribution coefficients Ⅰ, Ⅱ, Ⅲ, and Ⅳ, the optimal solution is 2-A2B2. From the perspective of the range R value, the order of priority is: B>A.

[0083] The results of intuitive analysis are consistent with those of computational analysis. Scheme A2B2 is the optimal scheme, that is, the polishing temperature is 62℃~68℃ and the polishing time is 16s~20s.

[0084] Polishing test appearance status picture see Figure 2 .

[0085] Anodizing formula and oxidation parameters experimental group - Experimental group 3

[0086] Two newly introduced pure sulfuric acid oxidation methods were used for oxidation experiments. In order to obtain oxide film pores suitable for dyeing, the oxidation temperature was controlled at 15℃~20℃. The process parameters were optimized based on the comparison of the experimental results.

[0087] Four levels of voltage A are selected: A1=12V; A2=13V; A3=14V; A4=15V; four levels of time B: B1=40min; B2=50min; B3=60min, B3=70min; and a factor level table is formulated as shown in Table 6.

[0088] Table 6 Factor level table

[0089]

[0090] Use L 16 (4 2 ) The orthogonal array for the experiment is shown in Table 7.

[0091] Table 7L 16 (4 2 )Orthogonal array

[0092]

[0093] According to the oxidation appearance of the parts (scoring criteria: whether the gloss is uniform (20 points), whether it is flat (10 points), whether there is local color difference (10 points), whether there are wrinkles (10 points), whether there are cracks (10 points), whether there are bubbles (10 points), whether there are marks (10 points), whether there are impurities (10 points), whether there are corrosion spots (10 points), formulate a process parameter experimental result analysis table, the full score is 100 points, see Table 8.

[0094] Table 8 Process parameter experimental results analysis table

[0095]

[0096]

[0097] Results Analysis

[0098] All experimental group numbers are prefixed with 3-XXX, where 3 represents experimental group number 3.

[0099] ①Intuitive analysis: From the experimental results, the experimental result of No. 9 is the best solution: 3-A1B3

[0100] (It can also be numbered 3-9. To facilitate orthogonal comparison, it is more convenient to number with letters).

[0101] ②Calculation and analysis: From the perspective of contribution coefficients Ⅰ, Ⅱ, Ⅲ, and Ⅳ, the optimal solution is 3-A1B3. From the perspective of the range R value, the priority order is: A>B.

[0102] The results of intuitive analysis are consistent with those of computational analysis. Scheme A1B3 is the preferred scheme. The concentration of sulfuric acid (H2SO4, mass fraction is 98%) is 200-220 g / L, the bath temperature is 15°C-20°C, that is, the oxidation voltage is 12 V, and the oxidation time is 60 min, which is the best scheme.

[0103] The thickness of the film layer of the anodized specimens was measured and counted by an eddy current thickness gauge. The three-point method was used to measure three groups of data on each specimen surface and take the average value. The average thickness was 10-15μm. The cross-cut method was used to determine the bonding strength. On the anodized film, 20 small squares of uniform size were scratched with a sharp blade at a spacing of 1mm (to ensure that the scratch depth exceeds the thickness of the film layer), and the number of squares that fell off was counted N1. A transparent tape was pasted on the cross-cut area on the film and pushed with a heavy object 5 times to ensure that the tape and the film were tightly bonded, and then it was lifted up and the number of small squares that fell off was observed and counted N2. The evaluation method is as follows: Using the percentage system, the bonding strength score of the film layer and the substrate is G=100-(N1+N2). The film bonding strength score is G=100.

[0104] The specific parameters of the dyeing process are: dyeing temperature 10°C ~ 40°C, dyeing time 10min ~ 30min.

[0105] The sealing solution used in the sealing process is an aqueous solution of 5-10g / l ODM SEAL EX sealing powder, the sealing temperature is 70℃~90℃, and the time is 10min~15min.

[0106] The aluminum alloy parts are surface treated by using the optimal formula and process parameters (such as Figure 1 As shown), the obtained parts were immersed in 95% ethanol and taken out after 2 hours. The color of the oxide film did not change. The dye absorption method was used to test the surface of the test piece with 1% alizarin red aqueous solution. After 5 minutes, it was washed and dried for observation. The surface color of the colored oxide film did not change significantly. The corrosion resistance was good. No corrosion occurred in the salt spray test for 96 hours. No corrosion occurred in the wet heat test for 240 hours (as shown). Figure 5 shown).

[0107] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing an oxide film layer on a matte sand surface of an aluminum alloy, characterized in that: Firstly, the aluminum alloy workpiece to be processed is subjected to sandblasting pretreatment and alkaline chemical polishing; then, a matte sand surface oxide film substrate is prepared by an anodic oxidation process; finally, the substrate is dyed and sealed to obtain a component with an aluminum alloy matte sand surface oxide film; The polishing liquid used in the alkaline chemical polishing contains sodium hydroxide, sodium nitrate, copper sulfate pentahydrate and triethanolamine.

2. The preparation method according to claim 1, characterized in that: The contents of the components of the polishing liquid are: 240-260 g / L of sodium hydroxide, 265-285 g / L of sodium nitrate, 2-3 g / L of copper sulfate pentahydrate, 10-20 ml / L of triethanolamine, and the solvent is water.

3. The preparation method according to claim 1, characterized in that: The specific process parameters of the alkaline chemical polishing are a polishing temperature of 62° C. to 68° C. and a polishing time of 16 to 20 seconds.

4. The preparation method according to claim 1, characterized in that: The sandblasting pretreatment process uses 80-100 mesh white corundum, and the sandblasting pressure is 0.5MPa-0.6MPa.

5. The preparation method according to claim 1, characterized in that: The anodizing process uses an oxidizing solution of 200-220 g / L sulfuric acid, an oxidation voltage of 12 V, an oxidation temperature of 15° C.-20° C., and an oxidation time of 60 min.

6. The preparation method according to claim 1, characterized in that: The specific parameters of the dyeing process are: dyeing temperature 10°C to 40°C, and dyeing time 10min to 30min.

7. The preparation method according to claim 1, characterized in that: The sealing solution used in the sealing process is 5-10 g / L ODM SEAL EX sealing powder, the sealing temperature is 70° C.-90° C., and the time is 10 min-15 min.

8. The preparation method according to claim 1, characterized in that: The aluminum alloy model is one of 6061, 6063, 7A04 and 7075.

9. The preparation method according to claim 1, characterized in that: The dye used in the dyeing process is YM-690, which is black in color.

10. An aluminum alloy component with a matte sand surface oxide film, characterized in that: The oxide film of the aluminum alloy component is prepared by the preparation method according to any one of claims 1 to 9.